2021
DOI: 10.1097/pra.0000000000000587
|View full text |Cite
|
Sign up to set email alerts
|

A Patient With Electroconvulsive Therapy–resistant Major Depressive Disorder With a Full Response to Heated Yoga: A Case Report

Abstract: Depression remains difficult to treat as a result of less than optimal efficacy and troublesome side effects of antidepressants. The authors present the case of a patient with treatment-resistant depression with melancholic features who had previously been unresponsive to electroconvulsive therapy (ECT) plus an antidepressant regimen but whose condition fully remitted with the addition of a standardized form of heated hatha yoga (HY; Bikram yoga) practiced in a room heated to 105°F. The patient was a 28-year-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…3 The 3 cases presented in this issue of the Journal deal with an array of clinical considerations in treating patients with TRD, including the use of ECT in a patient with a history of liver transplantation, the use of heated yoga (HY) in a patient nonresponsive to ECT, and a case of IN ketamine abuse. [4][5][6] Gunther et al 4 described the case of a 71-year-old man who had had an orthotopic liver transplant for hepatitis B and liver failure 26 years earlier and was admitted with a 2-month episode of major depressive disorder, severe, with psychotic features, that had not responded to an initial course of antidepressants. The authors cite the high rates of depression among patients after liver transplantation.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…3 The 3 cases presented in this issue of the Journal deal with an array of clinical considerations in treating patients with TRD, including the use of ECT in a patient with a history of liver transplantation, the use of heated yoga (HY) in a patient nonresponsive to ECT, and a case of IN ketamine abuse. [4][5][6] Gunther et al 4 described the case of a 71-year-old man who had had an orthotopic liver transplant for hepatitis B and liver failure 26 years earlier and was admitted with a 2-month episode of major depressive disorder, severe, with psychotic features, that had not responded to an initial course of antidepressants. The authors cite the high rates of depression among patients after liver transplantation.…”
mentioning
confidence: 99%
“…Sakurai et al 5 reported the case of a 28-year-old woman with a past mild traumatic brain injury and chronic TRD. The patient had had multiple (56) previous ECT treatments but continued to have only partial response to several antidepressants and maintenance ECT.…”
mentioning
confidence: 99%
See 3 more Smart Citations